Answer:
Option (3)
Explanation:
Given expression represents the sum of k terms of a geometric sequence.
![\sum_(k=1)^(9)2(4)^(k-1)](https://img.qammunity.org/2021/formulas/mathematics/college/8yvhxwwygsp5z1l8vfm3onix7392w6gtkh.png)
Since, formula to calculate the sum of a geometric sequence is given by,
![\sum_(n=1)^(n)a(r)^(n-1)=(a(1-r^n))/(1-r)](https://img.qammunity.org/2021/formulas/mathematics/college/xfh2jzi0sfg672xiycojz7m8h1jlc061d9.png)
By this formula,sum of 9 terms of the given sequence will be,
![\sum_(k=1)^(9)2(4)^(k-1)=(2(1-4^9))/(1-4)](https://img.qammunity.org/2021/formulas/mathematics/college/c4t6pps9kmkvr6x9vh63lvr64eoad3h6qn.png)
Therefore, Option (3) will be the answer.